Control of intestinal inflammation by regulatory T cells. - Toms, C; Powrie, F (2001)
Regulatory T(Treg)-cell populations have been identified in a number of disease models. In this review we focus on the role of naturally occurring Treg cells in the control of intestinal inflammation. Specifically, we discuss their mechanism of action with particular emphasis on the role of anti-inflammatory cytokines and cell surface molecules.